Six new cave-dwelling pholcid spiders (Araneae: Pholcidae) from Hainan Island, with two newly recorded genera from China - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2009)
Cave-dwelling pholcid spiders of Hainan Island, China are studied for the first time. Nine species, including six new species and one new recorded species from China, are reported, i.e. Belisana desciscens sp. nov., B. exian sp. nov., B. maogan sp. nov., B. yalong sp. nov., Holocneminus huangdi sp. nov., Modisimus culicinus (Simon, 1893) rec. nov., Pholcus exceptus sp. nov., Pholcus gui Zhu & Song, 1999, and Physocyclus globosus (Taczanowski, 1874). The genera Holocneminus and Modisimus both are newly recorded from China. All the six new species are diagnosed, described and illustrated. The newly recorded species Modisimus culicinus (Simon, 1893) is illustrated, too.